Environmental and socio-economic Pareto-front trade-off analysis of U.S. PET packaging material in a circular economy - Utkarsh S. Chaudhari; David W. Watkins; Robert M. Handler; Barbara K. Reck; Anne T. Johnson; Tasmin Hossain; Damon S. Hartley; Vicki S. Thompson; David R. Shonnard (Sustainable Production and Consumption, 2025)

Economic and environmental analysis of plastics pyrolysis after secondary sortation of mixed plastic waste - Daniel G. Kulas; Ali Zolghadr; Utkarsh S. Chaudhari; David R. Shonnard (Journal of Cleaner Production, 2023)

A Review of Environmental Life Cycle Assessments of Liquid Transportation Biofuels in the Pan American Region - David R. Shonnard; Bethany Klemetsrud; Julio Sacramento-Rivero; Freddy Navarro-Pineda; Jorge Hilbert; Robert Handler; Nydia Suppen; Richard P. Donovan (Environmental Management, 2015)

Estimation of soil carbon change from rotation cropping of rapeseed with wheat in the hydrotreated renewable jet life cycle - Suchada Ukaew; Emily Beck; David W. Archer; David R. Shonnard (The International Journal of Life Cycle Assessment, 2015)

Assessment of the Automobile Assembly Paint Process for Energy, Environmental, and Economic Improvement - Geoffrey J. Roelant; Amber J. Kemppainen; David R. Shonnard (Journal of Industrial Ecology, 2004)
A coat of paint adds considerable value to an automobile. In addition to consuming up to 60% of the energy needed by automobile assembly plants, however, the painting process also creates both economic and environmental impacts. This study investigated the degree of cost and environmental impact improvement that can be expected when modifications are considered for existing paint processes through heat integration. In order to accomplish this goal, a mathematical model was created to describe the energy use, costs, and environmental impacts from energy consumption in an automobile assembly painting facility. The model agrees with measured energy consumption data for process heating and electricity demand to within about 15% for one Michigan truck facility from which model input parameters were obtained. Thermal pinch analysis determined an energy conservation target of 58% of paint process energy demand. A heat exchanger network optimization study was conducted in order to determine how closely the network design could achieve this target. The resulting heat exchanger network design was profitable based on a discounted cash flow analysis and may achieve reductions in total corporate energy consumption of up to 16% if implemented corporatewide at a major automobile manufacturer.

US EPA/academia collaboration for a green engineering textbook for chemical engineering - David R. Shonnard; David T. Allen; Sharon Austin; Nhan Nguyen (Clean Technologies and Environmental Policy, 2003)